Breakthrough Radical Innovation From An Islamic Perspective: A Literature Review - Dwi Retna Sulistyawati; Tri Handayani; Rita Andini; Sukamto Sukamto; Heri Poerbantoro (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Radical innovation is a breakthrough change in the overall pattern of the old system, as a form of implementing new ideas to achieve a competitive advantage. Radical innovation is a solution to escape from external environmental pressures in the form of competition, deregulation in the industry, scarcity of resources, and higher customer demands. This study builds a conceptual model from an Islamic point of view: the value of maslahah in all cases provides benefits or goodness from radical innovation. Maslahah means the good rewards promised by God in this world and the hereafter, thus maslahah implies the benefits of this world and the hereafter, which encourages people to always think and produce new things that are beneficial.